2017
DOI: 10.17718/tojde.285719
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Social Media Use on Collaborative Learning: A Case of Turkey

Abstract: The social media usage has penetrated to the many areas in daily lives of today's students. Therefore, social media can be effective tool to support their educational communications and collaborations with their friends and also faculty members. This study aims to determine the effects of social media on collaborative learning. For this purpose, a theoretical model is proposed based on comprehensive literature review. Using an online questionnaire, data are collected from the students of one of the largest uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 11 publications
(19 reference statements)
2
33
1
2
Order By: Relevance
“…Therefore, it allows learners to be connected to their language education, ask questions, provide responses, perform peer corrections, give comments, and even share knowledge anywhere and anytime online (Chandler & Redman, 2013;Crowe & McDonald, 2013;Lara, 2013). In so doing, it fosters interaction and cooperation among students, course engagement, and students-teacher interactions which can be difficult to achieve in a physical classroom (Bozanta & Mardikyan, 2017;Sandu, 2015). However, it seems that a combination of traditional in-class instruction and online sessions via Edmodo is considered to be an effective factor in generating more positive attitudes towards learning English (Alseweed, 2009;Bersin, 2004).…”
Section: Implementation Of Edmodo In Language Teaching and Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it allows learners to be connected to their language education, ask questions, provide responses, perform peer corrections, give comments, and even share knowledge anywhere and anytime online (Chandler & Redman, 2013;Crowe & McDonald, 2013;Lara, 2013). In so doing, it fosters interaction and cooperation among students, course engagement, and students-teacher interactions which can be difficult to achieve in a physical classroom (Bozanta & Mardikyan, 2017;Sandu, 2015). However, it seems that a combination of traditional in-class instruction and online sessions via Edmodo is considered to be an effective factor in generating more positive attitudes towards learning English (Alseweed, 2009;Bersin, 2004).…”
Section: Implementation Of Edmodo In Language Teaching and Learningmentioning
confidence: 99%
“…Multiple studies have focused on university students' perceptions of Edmodo-enhanced instruction. The use of this new technology, has introduced an innovative scenario to the traditional instruction which resulted in positive perceptions towards Edmodo and MALL since it facilitates collaborative learning and students' self-confidence (Bozanta &Mardikyan, 2017;Yunkul & Cankaya, 2017). It also increases effectiveness of communication and language learning (Al-Said, 2015; Al- Shammari, 2007;Mokhta & Dzakiria, 2015;Sandu, 2015;Thongmak, 2013).…”
Section: Students' Perceptions Of Edmodomentioning
confidence: 99%
“…This inappropriateness becomes one of failure factors in education now (Kabir & Kadage, 2017). An effective interaction among teachers, students, learning sources, learning media which utilize mobile technology becomes a success key in the learning competence achievement (Bozanta, 2017;Furberg, 2016;Kashorda, et al, 2007;Sadaf et al, 2016;Yadegaridehkordi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In Turkey, school media activities are based primarily on collaboration between teachers and students through exploring practical applications of the curriculum to increase students' academic attainment (Cakmak, Tuzel, 2015). Educational media in Turkish schools aims at promoting collaborative learning, especially since students use media with ease (Bozanta, Mardikyan, 2017). In this respect, a study conducted by Palavan (Palavan, 2017) on a sample of Turkish students revealed that educational theatre and drama were the prominent media activities that had positive effects on students' self-confidence and problem-solving skills.…”
Section: Discussionmentioning
confidence: 99%